Determinants of donations received by charities : a case study on RDA Singapore. - Neo, Yi Xiang. (2008)
The objective of this paper is to examine the factors that influence the donations received by the Riding for the Disabled Association of Singapore (RDA). The factors are studied in two parts; the first pertains to the investigation of macro-level factors, while the second looks at micro-level factors.